DESENVOLVIMENTO E AVALIAÇÃO FARMACOLÓGICA IN VITRO DE NANOCÁPSULAS CONTENDO ÓLEO DE Astrocaryum vulgare NO REPARO TECIDUAL CUTÂNEO - Riéffel, Roberta Cougo (2019)
The skin is the largest organ of the human body and performs numerous functions, the absence of the skin barrier predisposes to infections, increased transepidermal loss of substances and hypothermia, which may sometimes cause increased morbidity and prolonged hospitalizations. The country's biodiversity has generated a considerable knowledge mechanism, including data on the medicinal properties of assets, which receive attention due to their low cost, safety and therapeutic efficacy. In an attempt to reduce the use of systemic drugs, new technologies and the use of natural products are being researched as resources for the prevention and treatment of skin lesions. Tucumã oil has a wide range of natural substances with anti-inflammatory capacity and probable healing properties such as beta-carotene, oleic, linoleic, linolenic fatty acids, as well as polyphenols and tocopherol. Nanotechnology allies to preserve these constituents and still offer a gradual delivery of bioactive to tissue. The objective of this study was to develop optimized oil-core polymer nanocapsules with reduced amount of surfactants and polymer containing tucumã oil, to analyze their physicochemical properties and stability. For in vitro experimental tests, peripheral blood mononuclear cells, erythrocytes, HFF-1, HaCaT and RAW were used. The pharmacological safety, efficacy, anti-inflammatory, antioxidant and healing activity of tucumã nanocapsules were analyzed. MTT assay, dichlorofluoriscein diacetate test, green peak genotoxicity, nitric oxide test, superoxide anion radical assay, quantification of caspases 3 and 8, cytokines IL-1, IL-6, TNF-α, were used. INF-γ, IL-10, Glutathione S-transferase antioxidant enzyme activity, Glutathione peroxidase, Superoxide dismutase, FGF and KGF growth factor evaluation and in vitro Scratch assay. The concentrations of 10 and 30 μg / mL were the safest and most effective, showed cell viability, anti-inflammatory action, showed cell proliferation capacity and increased FGF and KGF growth factors, did not increase the rate of cell apoptosis, suggesting a anti-inflammatory and healing profile. The nanocapsule suspension was spray dried and when characterized maintained its physicochemical characteristics.